A holistic view of the Holy Spirit as agent of ethical responsibility: This view experienced as exciting in Romans 8, but alarming in 1 Corinthians 12 - Vledder, E. J. (Hervormde teologiese studies, 1991)
Modern man experiences a crisis which manifests itself across a wide spectrum: ecologically, sociologically and politically. Seen from a holistic perspective, this crisis, caused by the so-called mechanical worldview, calls for a radical change to a new worldview, the so-called postmodern or holistic view. In ecumenical theology, emphasis is also laid on the world in crisis, which calls for renewal on the same levels as in holistic thought. This change and renewal is to be brought about by the Holy Spirit, who is the agent of change in thought, and of involvement in creating a ‘new creation’. It will be argued that the Holy Spirit is indeed involved as the agent of man’s ethical responsibility; in Romans 8:1-17 this is seen as exciting, but, in 1 Corinthians 12:1-11, the alarming danger in ecumenical pneumatology is indicated.